Role of a support network for refugee mothers - ACHING, Michele Carmona (2023)
Recent studies on the transition to motherhood suggest that a support network plays a central role in maternal experience and in the development of the mother-infant relationship. Being a woman without a partner, having economic diffi culties, belonging to an ethnic minority or being a recent migrant are some of the conditions that overlap with the demands of maternity and create multiple vulnerabilities. This article analyzes the maternal experience of two recent refugee women in Brazil. The analysis is based on psychotherapeutic sessions at a Winnicottian transcultural clinic offered at a host institution for pregnant women and mothers. We describe how loneliness and helplessness challenge maternal skills, while resilience and adequate shelter facilitate the construction of a support network that favors good motherhood. In our view, the professional can help ensure that maternal practices are guided by the cultural reference of origin as the mother integrates into the culture of the host country.